Training time and adaptation to lack of day light : a case report - G. Calogiuri; E. Roveda; A. Montaruli; F. Carandente; S. Beldo; A. Weydahl (Sport Sciences for Health, 2009)
A pilot study was conducted to describe the reaction to lack of daylight and different training times of circadian rhythms and sleep in a subject arriving in Alta (Northern Norway) from Milan (Italy) in the darkness period. Monitoring sessions by heart rate (HR) monitor and actigraph were performed after four conditions: MS1, no training in Italy; MS2, no training in Alta (lack of daylight); MS3, evening training in Alta; and MS4, morning training in Alta. Midline Estimating Statistic Of Rhythm (MESOR) for activity was lower in MS2 than in MS1, MS3 and MS4, and decreased progressively for HR. Acrophases were advanced in MS2 and MS4 compared to MS1 and MS3 for both activity and HR. Sleep Efficiency was higher in MS2, MS3 and MS4 compared to MS1, coinciding with low values in the Mean Activity Score and Movement and Fragmentation Index. It could be seen that lack of daylight induced a decrease of the activity state in the subject, advancing the acrophase and leading to increased sleep. After the exercise sessions the activity state of the subject increased and the circadian structure was influenced according to the time at which the training was performed.